Effective Lead Ions (Pb2+) Mitigation in Battery Industry Wastewater via NaOH-Activated Water Hyacinth (Eichhornia crassipes) - Hibatulwafi, Chintya Mahjati; Sari, Dessy Agustina; Wahyuningtyas, Aulia (Universitas Trunojoyo Madura, 2024)
Lead, which is one of the most important heavy metals, is a worldwide toxic pollutant. Adsorption is one of the methods used to study the removal of heavy metal ions from solutions, which encourages us to study the reduction of Pb2+ concentrations in wastewater from the battery factory in this study. The best conditions for adsorption were found using a bioadsorbent called 0.5 M NaOH-activated water hyacinth. This was studied using FTIR to identify the plant. This research conducted adsorption tests on a 20 ppm Pb2+ standard solution, varying the contact times to 20, 30, 40, 50, 60, 70, 140, 210, and 280 minutes. At the contact time of 140 minutes, the Pb2+ concentration reduced to 0.1558 ppm with a 98.0881% adsorption efficiency. Before the bioadsorbent treatment, the FTIR analysis of O-H, C-H, C=C, and C-O functional groups showed that cellulose was present. Activation eliminates the C=C peak and reduces the intensity of the O-H peak. This shows that the lignin and hemicellulose chains are breaking down. When the bioadsorbent binds to Pb2+, the vibrational frequencies of the C-H and C-O groups change, which shows that it works. The results show that the water hyacinth bioadsorbent activated by NaOH is a good alternative material for dealing with Pb2+ waste, which lowers the amount of lead in industrial waste water by a large amount.